The teaching brain : an evolutionary trait at the heart of education - Rodriguez, Vanessa, 1976-; Fitzpatrick, Michelle (The New Press, 2014)
"What is at work in the mind of a five-year-old explaining the game of tag to a new friend? What is going on in the head of a thirty-five-year-old parent showing a first-grader how to button a coat? And what exactly is happening in the brain of a sixty-five-year-old professor discussing statistics with a room full of graduate students? While research about the nature and science of learning abounds, shockingly few insights into how and why humans teach have emerged--until now. Countering the dated yet widely held presumption that teaching is simply the transfer of knowledge from one person to another, The Teaching Brain weaves together scientific research and real-life examples to show that teaching is a dynamic interaction and an evolutionary cognitive skill that develops from birth to adulthood. With engaging, accessible prose, Harvard researcher Vanessa Rodriguez reveals what it actually takes to become an expert teacher. At a time when all sides of the teaching debate tirelessly seek to define good teaching--or even how to build a better teacher--The Teaching Brain upends the misguided premises for how we measure the success of teachers. This game-changing analysis of how the mind teaches will transform common perceptions of one of the most essential human practices (and one of the most hotly debated professions), charting a path forward for teachers, parents, and anyone seeking to better understand learning--and unlocking the teaching brain in all of us"--